2011
DOI: 10.3402/edui.v2i3.21990
|View full text |Cite
|
Sign up to set email alerts
|

Liberating the Mind or Governing the Soul? Psychotherapeutic Education, Children’s Rights and the Disciplinary State

Abstract: Education Inquiry is an international on-line, peer-reviewed journal with free access in the field of Educational Sciences and Teacher Education. It publishes original empirical and theoretical studies from a wide variety of academic disciplines. As the name of the journal suggests, one of its aims is to challenge established conventions and taken-for-granted perceptions within these fields. Education Inquiry is looking for lucid and significant contributions to the understanding of contextual, social, organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 23 publications
0
37
0
Order By: Relevance
“…Other interventions promoted in the schools to reduce the risk of depressive disorders in children and adolescents are psychoeducational courses (Merry et al, 2009). However, critical research has shown that such courses pathologize young people, labeling them as 'at risk' and making mental problems a question of individual deficiencies (Coppock, 2011;Dahlstedt et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other interventions promoted in the schools to reduce the risk of depressive disorders in children and adolescents are psychoeducational courses (Merry et al, 2009). However, critical research has shown that such courses pathologize young people, labeling them as 'at risk' and making mental problems a question of individual deficiencies (Coppock, 2011;Dahlstedt et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Policy-makers and Government authorities in industrialized countries invest in policy initiatives and courses aimed at promoting children's mental health (Coppock, 2011;Hoffman, 2009;Wishart et al, 2006;Dahlstedt et al 2011). Although a clear majority of young people report good mental health, efforts to promote children's mental health and emotional wellbeing have largely been developed as universal and preventive interventions in the schools (Coppock, 2011). As a result numerous pedagogical programs have been marketed, such as Social emotional learning (SEL), which aims to teach all students fundamental social and emotional competencies (Hoffman, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…2 The initiative to implement socio-emotional programmes in schools is driven by a prevention discourse suggesting that such programmes provide effective means to prevent mental ill-health 3 in young people and to promote the future well-being of the population by 'intervening before minor problems develop into major ones' (Wright, 2015, p. 212). 4 Little is known, however, about what these interventions entail 'here and now' for the students experiencing them in school (Coppock, 2011;Irisdotter Aldenmyr, 2014b;Watson et al, 2012). The present study intends to address this issue by trying to understand students' perspectives on socio-emotional programmes (DISA and SET) as well as the programmes' intentions and strategies.…”
Section: Introductionmentioning
confidence: 97%
“…The programmes are underpinned by discourses focusing on a crisis in young people's mental health and a will to foster healthy citizens (Coppock, 2011;Watson et al, 2012). 1 Depression in Swedish Adolescents (DISA) and Social and Emotional Training (SET) constitute two socioemotional programmes being practised in Swedish schools.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation